Becoming like us : Conversion and Penan-ness at Long Beruang, Sarawak - Valerie, Mashman; Poline, Bala (Liverpool University Press, 2023)
How did the Penan of Sarawak, East Malaysia stop their nomadic life and become settled farmers and retain their identity as Penan? This article presents the memories of settled Kelabit and the neighbouring Penan of a time when they were reluctant to meet one another, when the Penan were nomadic. Their lifestyles were very different: the Penan were wary of outsiders, and the Kelabit children were scared of the Penan. The processes which brought about change between these two groups were motivated by the Kelabit urge to evangelise to the Penan. They began meeting and sharing food. Gradually, the Kelabit farmers encouraged the Penan ‘to become like us’, to settle as their neighbours at Long Beruang and become Christians like them. Eventually the Penan became successful padi-farmers and made their livelihood from both the forest where they hunted and foraged and from the padi fields where they grew rice. However, this did not lead to the assimilation of the Penan by the Kelabit but to a greater deliberate expression of Penan identity. This appears to be in keeping with phenomena elsewhere in the world, which suggest that when an ethnic group is under threat from external forces and assimilation, people assert their ethnic identity.